Удосконалення технологічної схеми очищення зворотних вод авіапідприємств - Маджд, С. М. (КНУБА, 2013)
Розроблені водоохоронні заходи для підвищення екологічної безпеки підприємств з експлуатації та ремонту авіаційної техніки. Здійснена оцінка ефективності роботи очисних споруд об'єктів цивільної авіації. Удосконалена технологічна схема очистки стічних вод авіатранспортних підприємств. Разработаны водоохранные мероприятия для повышения экологической безопасности предприятий из эксплуатации и ремонта авиационной техники. Осуществлена оценка эффективности работы очистных сооружений объектов гражданской авиации. Усовершенствованная технологическая схема очистки сточных вод авиатранспортных предприятий. The worked out bank-protection measures are for the increase of ecological safety of enterprises from exploitation and repair of aerotechics. Realizable estimation of efficiency of work of sewage treatment plants of objects of civil aviation. Improved flowsheet of cleaning of effluents of air enterprises.
Improvement of technological scheme cleaning of reverse waters of airenterprises
Усовершенствование технологической схемы Очистки обратных вод авиапредприятий
Keywords: водоохоронні заходи; очистка стічних вод; екологічна безпека авіапідприємств; забруднення; важкі метали; нафтопродукти; водоохранные мероприятия; очистка сточных вод; экологическая безопасность авиапредприятий; загрязнение; тяжелые металлы; нефтепродукты.; bank-protection measures; cleaning of effluents; pollution; heavy metals; hydrocarbons; environmental safety of enterprises for exploitation and repair of aviation techniques; 656.71:504.4